“可爱” 又 “可恶” 的女人 ：中国广场舞大妈 = Adorable or abominable? : Chinese square dancing dama - 徐昕 Xin, Xu (2017)
近年来，广场舞作为一种全民健身活动，风靡全中国。广场舞活动的参与者大多是中老年妇女，人们称她们为广场舞大妈。本文试图探讨广场舞大妈热衷于广场舞的缘由，她们所承担的社会功能以及跳广场舞所引发的冲突矛盾。本文认为，广场舞大妈热衷于广场舞的基本初衷是想强身健体，其次，寻求家庭结构变化导致的归属感的缺失，寻求消除退休带来的冷落不适感以及共同拥有的集体化时代的历史记忆，是广场舞大妈选择广场舞的多元动机。广场舞大妈在参与广场舞活动时，无意中承担了社会功能，为所在街道社区争得荣誉，她们基于对广场舞的热爱而形成的广场舞趣缘群体，不仅拉近了邻里关系，还能在潜移默化中推动社会和谐发展。然而，广场舞大妈与周边居民的矛盾冲突频频发生，这主要是因为中国在迅速城市化过程中，形成了紧凑的城市功能形态、土地混合使用以及追求利益最大化而忽略人们的根本需求，导致噪音扰民、抢夺地盘等城市治理难题。要解决广场舞与城市空间的紧张关系，应当重新审视广场舞的文化价值、提高休闲公共空间的管理及出台相应法规，从而改善人们的体育休闲环境。 In the recent years, Square dancing has become a popular group exercise for the mass public and the wave has hit the whole of China. Participants of square dancing are mainly female ranging from middle to old age. They are often name as square dancing "dama". This article gives us a look into what made the square dancing "dama" so passionate about square dancing in the beginning. There's an inverse relation to their status and capability in the workplace in regard to square dancing. This article tries to find that square dancing is so enticing to the square dancing "dama" due to its overall health benefits. In another words, square dancing gives them a sense of belonging which is often lost in the process of family progression. These "dama" seeks to replace the loneliness that retirement brings and also to forge a bond with fellow square dancers that would last until their time is up. These are some of the reason and motive square dancing is one of the chosen exercises over other exercises. Square dancing has empowered the square dancing "dama" with high society value by glorifying their communities through their square dancing events. Their passion towards square dancing served as a deep, entrenched foundation for the community and formed an interest-related group. Which further propels the community go achieve greater unity through the bonds that is created within Square dancing. However, conflicts still arises with neighbors in the community due to China's increasing demand in the standard of living, couple with closely packed city developments aimed at multi function space. In order to maximize profits, these initiatives neglected the basic necessity and well being of a human being. Solution to urban spatial of mass leisure activities should be re-examine the cultural value of Square dancing, more efficient management of spaces in the cities, as well as implementation of rules and regulation to cater to the needs of the citizens in terms of their health and emotional well-being.